Thermal Management and Modeling of Forced Convection and Entropy Generation in a Vented Cavity by Simultaneous Use of a Curved Porous Layer and Magnetic Field - Selimefendigil, Fatih; Öztop, Hakan Fehmi E. (Mdpi, 2021)
The effects of using a partly curved porous layer on the thermal management and entropy generation features are studied in a ventilated cavity filled with hybrid nanofluid under the effects of inclined magnetic field by using finite volume method. This study is performed for the range of pertinent parameters of Reynolds number (100 <= Re <= 1000), magnetic field strength (0 <= Ha <= 80), permeability of porous region (10(-4) <= Da <= 5 <= 10 2), porous layer height (0.15 H <= tp <= 0.45H), porous layer position (0.25 H <= yp <= 0.45 H), and curvature size (0 <= b <= 0.3 H). The magnetic field reduces the vortex size, while the average Nusselt number of hot walls increases for Ha number above 20 and highest enhancement is 47% for left vertical wall. The variation in the average Nu with permeability of the layer is about 12.5% and 21% for left and right vertical walls, respectively, while these amounts are 12.5% and 32.5% when the location of the porous layer changes. The entropy generation increases with Hartmann number above 20, while there is 22% increase in the entropy generation for the case at the highest magnetic field. The porous layer height reduced the entropy generation for domain above it and it give the highest contribution to the overall entropy generation. When location of the curved porous layer is varied, the highest variation of entropy generation is attained for the domain below it while the lowest value is obtained at y(p) - 0.3 H. When the size of elliptic curvature is varied, the overall entropy generation decreases from b = 0 to b = 0.2 H by about 10% and then increases by 5% from b = 0.2 H to b = 0.3 H.
Keywords: curved porous layer; vented cavity; convection; finite volume method; nanofluid; entropy generation